Landscape gene flow of demethylase inhibitor resistance in Pyrenophora teres f. teres - Hodgson, Leon Marc (Curtin University, 2023)
Fungicide resistance in foliar fungal pathogens is an emerging issue to sustainable agricultural production. Current management options are limited by a lack of knowledge of the gene flow of resistance. Sampling strategies and molecular tools were developed to enable accurate quantification of the demethylase inhibitor resistance gene in Pyrenophora teres f. teres. The landscape distribution and gene flow of demethylase inhibitor resistance were then determined, which inform fungicide resistance management choice.